Evaluasi Kualitas Air Sungai Ayung Metode WQI (Water Quality Index) Sebagai Dasar Penanganan Pencemaran dan Rekomendasi Pengelolaan Sungai - Chintya Arivany; Putu Indah Dianti Putri; I Putu Prana Wiraatmaja; I Ketut Nuraga (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Ayung River is the longest river in Bali Island and plays a strategic role as a source of raw water, irrigation, tourism support, and aquatic ecosystems. However, increasing domestic, agricultural, and tourism activities along the watershed have exerted significant pressure on water quality. This study aims to evaluate the water quality status and pollution level of the Ayung River using the Water Quality Index (WQI) by considering temporal variations (seasonal, annual, and five-year trends) as well as spatial variations among monitoring stations, and to formulate river management recommendations. The study employed secondary water quality data from 2020–2024 collected at seven monitoring stations, including pH, DO, BOD, COD, and TSS parameters, which were analyzed using the WQI method in reference to Class II water quality standards. The results indicate that the overall water quality of the Ayung River falls within the Poor (C) category, exhibiting temporal fluctuations without a consistent long-term improvement trend. Spatially, the upstream segment shows relatively better water quality compared to the middle and downstream segments, indicating an accumulation of pollutant loads toward the downstream areas. Organic pollutants, particularly BOD and COD, were identified as the dominant factors contributing to water quality degradation. These findings highlight the need for integrated and adaptive management strategies focused on controlling organic pollutant loads based on seasonal conditions and river segments to improve the water quality of the Ayung River sustainably.